2006
DOI: 10.1111/j.1463-6395.2006.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of plasminogen‐like protein in amphioxus with implications for the origin of vertebrate liver

Abstract:  Abstract Liang, Y.J. and Zhang, S.C. 2006. Demonstration of plasminogen-like protein in amphioxus with implications for the origin of vertebrate liver. -Acta Zoologica (Stockholm) 87 : 141-145Plasminogen, the proenzyme of serine protease plasmin, is a plasma glycoprotein synthesized primarily in the liver, and its evolutionary origin in chordates remains unclear. We demonstrated here that the humoral fluid in amphioxus is capable of cross-reacting with anti-human or anti-mouse plasminogen antibodies, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…It is of note that BbPlgl has a calculated molecular mass of approx. 46.7 kDa, which is about half the size of that estimated from Western blotting analysis [19]. Although this difference may be due to the fact that the molecular mass calculated from BbPlgl cDNA has ignored the putative glycosylations, it cannot be ruled out that BbPlgl and the molecule reported by Liang and Zhang [19] are two different molecules.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…It is of note that BbPlgl has a calculated molecular mass of approx. 46.7 kDa, which is about half the size of that estimated from Western blotting analysis [19]. Although this difference may be due to the fact that the molecular mass calculated from BbPlgl cDNA has ignored the putative glycosylations, it cannot be ruled out that BbPlgl and the molecule reported by Liang and Zhang [19] are two different molecules.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have shown the presence of Plg only in the jawed vertebrates [3,32], and a Plgl molecule has been discovered in the amphioxus B. belcheri, a basal chordate [19]. However, molecular mammalian Plgs [23], BbPlgl is also able to auto-activate at neutral and alkaline pH at 4 • C without the addition of human uPA, and the activation is remarkably accelerated by addition of human uPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detail the distribution of BMP2/4 at the wound site, immunohistochemical staining was also conducted on tissue sections of tail regenerates at the wound-healing stage. Processing and immunostaining of the sections was conducted as described previously (Liang and Zhang, 2006). The primary antibody was diluted 1:400 and the secondary antibody (HRP-conjugated goat anti-rabbit IgG; Abcam, ab97051) was diluted 1:600.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…If this is correct, it might then be analogous to the so‐called mid‐gut diverticulum of amphioxus (e.g. Barrington, 1937; see also Liang & Zhang, 2006), although this of course is located on the opposite side of the body. Finally, we should note that the amphioxus has no obvious equivalent to the structure(s) identified as the anterior dorsal unit.…”
Section: Phylogenetic Relationships Of Pikaiamentioning
confidence: 99%